2015
DOI: 10.4172/2157-7560.1000276
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Immunological Characterizations of the Receptor Binding Domain of C. difficile Toxin B

Abstract: Clostridium difficile (Cd) is an emerging nosocomial pathogen responsible for antibiotic-associated pseudomembranous colitis and diarrhea in hospital acquired infections. Clostridial toxins A (TcdA) and B (TcdB) which specifically bind to unknown glycoprotein(s) on the surface of epithelial cells disrupt the intestinal barrier and ultimately lead to acute inflammation and diarrhea. There is still debate as to whether the receptor binding domains (RBD) of toxins can individually elicit protection in the hamster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 48 publications
3
9
0
Order By: Relevance
“…The circular dichroism (CD) secondary structure analysis of rlipoA-RBD was also performed and found that rlipoA-RBD had correctly folded to form β-sheet structure similar to A-rRBD (>43 %) [ 30 ]. This result is consistent with other reports that RBD forms stable folded β-solenoid secondary structures independently of other functional domains in the TcdA [ 30 , 31 ]. Although a simple and rapid method for producing rlipoA-RBD with high purity was successfully developed, rlipoA-RBD was found to be unstable and showed a loss in biological function during the freeze-thaw process.…”
Section: Resultssupporting
confidence: 94%
See 4 more Smart Citations
“…The circular dichroism (CD) secondary structure analysis of rlipoA-RBD was also performed and found that rlipoA-RBD had correctly folded to form β-sheet structure similar to A-rRBD (>43 %) [ 30 ]. This result is consistent with other reports that RBD forms stable folded β-solenoid secondary structures independently of other functional domains in the TcdA [ 30 , 31 ]. Although a simple and rapid method for producing rlipoA-RBD with high purity was successfully developed, rlipoA-RBD was found to be unstable and showed a loss in biological function during the freeze-thaw process.…”
Section: Resultssupporting
confidence: 94%
“…We have previously reported that both A-rRBD and B-rRBD at 0.8 −1 μM have strong abilities to up-regulate cell surface marker expression and cytokine secretion from BMDCs [ 30 , 31 ]. To enhance the effectiveness of A-rRBD as a recombinant subunit vaccine candidate against CDI, A-rRBD was rationally designed and lipidated (rlipoA-RBD) to contain a toll-like receptor 2 agonist (intrinsic adjuvant) [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations